A Targeted Approach for Building a Secure Air-Gapped System - Siahloui, Esmail; Tabatabaei Manesh, Seyed Reza (Management Strategies and Engineering Sciences, 2025)
This study aims to present a targeted strategy for developing a methodology that leads to the design and implementation of an air-gapped system. The research integrates existing technologies from the fields of physics, cybersecurity, data transmission, physical protection, cryptography, and encoding. This paper is based on studies conducted on attacks targeting air-gapped systems, identifying vulnerabilities in each system, and subsequently proposing a solution. To achieve this, over 150 reputable global research articles were reviewed. In air-gapped systems, networked computer communications—whether wired or wireless—between the internal and external environments do not exist. As a result, these systems offer a higher level of security. However, studies indicate that they may still be vulnerable. This paper attempts to introduce a method that results in the creation of a structured list of tasks. Following this list aligns with organizational objectives for establishing an air-gapped system and ultimately leads to the design and implementation of such a system.